Detailed Genome Screening of a Highly Efficient Diploid Alfalfa Symbiont Ensifer meliloti L6-AK89 - Roumiantseva, Marina L.; Vladimirova, Maria E.; Saksaganskaia, Alla S.; Muntyan, Victoria S.; Kozlova, Alexandra P.; Afonin, Alexey M.; Baturina, Olga A.; Simarov, Boris V. (Research Advances and Challenges in Agricultural Sciences Vol. 6, 2024)
A detailed analysis of the accessory part of the genome of the economically promising Ensifer (Sinorhizobium) meliloti strain L6-AK89, a symbiont of Medicago lupulina, was obtained by next-generation high-throughput sequencing (MiSeq, MinION). L6-AK89 is a StrR mutant of the native isolate CIAM1775, which formed pink large nodules on the roots of M. lupulina growing in soil subject to secondary salinization in northern Kazakhstan. Inoculation of M. lupulina cv. Mira (fodder-type standard) with strain L6-AK89 allows to guarantee the increase of plant dry weight in vegetation experiments on moderately acidic soils of humid agricultural zones by at least 150%. The genome of L6-AK89 has one and a half times increased share of sequences associated with elements of the accessory part of the genome relative to the reference strain Rm1021. The data of analysis of 53 genes responsible for symbiotic and nitrogen-fixing activity and 32 genes involved in response to stress factor (salinity) are presented, which were compared with the analysis of 16S rRNA gene and a concatenate of core genes, recA-atpD-glnII-gyrB-dnaJ. It was concluded that the genome of the symbiotically highly efficient strain L6-AK89 contains unique structural differences in genes that may mediate the control of symbiotic properties and the formation of response to abiotic stress factors, and it also contains unique clusters of quorum-sensing and osmoprotector synthesis genes.